Nephroprotective Effect of Spermacoce hispida by reducing Oxidative and Nitrosative Stress in Experimental Model - Sitafale, Gopal; Jat, Rakesh Kumar; Pathan, Amjad Khan; Biyani, Kailas (Journal of Drug Delivery and Therapeutics, 2022)
Present study was aimed to investigate the protective of Spermacoce hispida in Cisplatin induced nephrotoxicity using in vivo model. S. hispida was collected and extract of plant was prepared in different solvents and prepared extracts was used for phytochemical scrrening. Nephrotoxicity in rats was induced by a single intraperitoneal injection of Cisplatin at a dose of 5 mg/kg. S. hispida extract in different solvent at the dose 100 mg/kg used to find protective activity. Blood urea nitrogen (BUN), serum creatinine, oxidative stress, a proinflammatory cytokine, NO, and histological alteration was measured to estimate the therapeutic ability of S. hispida. BUN, creatinine, and inflammatory cytokine levels in rats were increased by Cisplatin but decreased by S. hispida treatment for 14 days. Besides, S. hispida treatment decreased oxidative stress and nitric oxide in Cisplatin-treated rats. Cisplatin treated rats shows altered structure of kidney tissue; meanwhile S. hispida normalizes the structure of kidney tissue. From this study, we conclude that S. hispida has nephroprotective activity by inhibiting the oxidative stress and NO production in rats from nephrotoxicity. Keywords: Spermacoce hispida; Cisplatin; oxidative stress; Cytokine; Nitric oxide.